Pelanggaran Etika Pariwara dalam Iklan Judi Online di Situs Live Streaming dan Poster Sepak Bola - Fauzan, Muhammad; Ramadani, Aliya Putri; Sashi, Adena; Junaedi, Fajar (Jurnal Riset Komunikasi (JURKOM), 2025)
This study seeks to examine ethical breaches in advertising inside online gambling promotions on live streaming platforms and football posters. This study employs a qualitative descriptive research method. The data collecting involved the documentation of live streaming platforms and football match advertisements. The gathered data was examined through the lens of diverse ethical theories and advertising restrictions. This study determined that online gambling advertisements sent via live streaming platforms and football match posters distinctly contravene advertising ethical standards and regulatory rules in Indonesia. These advertising manipulate the audience's psychological vulnerabilities by deceptive persuasive techniques, including promises of substantial profits, the employment of popular symbols, and promotions including little starting prices. Advertisements are disseminated in media readily accessible to vulnerable populations, including children and adolescents, devoid of age limitations or risk warnings, so undermining the principle of social responsibility in communication ethics.